A novel missense variant in ESRRB gene causing autosomal recessive non-syndromic hearing loss: in silico analysis of a case - Tohid Ghasemnejad; Mahmoud Shekari Khaniani; Jafar Nouri Nojadeh; Sima Mansoori Derakhshan (BMC, 2022)
Abstract Background Hereditary hearing loss (HHL) is a common heterogeneous disorder affecting all ages, ethnicities, and genders. The most common form of HHL is autosomal recessive non-syndromic hearing loss (ARNSHL), in which there is no genotype-phenotype correlation in the majority of cases. This study aimed to identify the genetic causes of hearing loss (HL) in a family with Iranian Azeri Turkish ethnicity negative for gap junction beta-2 (GJB2), gap junction beta-6 (GJB6), and mitochondrially encoded 12S rRNA (MT-RNR1) deleterious mutations. Methods Targeted genome sequencing method was applied to detect genetic causes of HL in the family. Sanger sequencing was employed to verify the segregation of the variant. Finally, we used bioinformatics tools and American College of Medical Genetics and Genomics/Association for Molecular Pathology (ACMG/AMP) guidelines to determine whether the detected variant might affect the corresponding protein or not. Results A novel homozygous missense mutation, c.499G>A (p.G167R), was identified in exon 5 of the ESRRB (estrogen-related receptor beta) gene. Healthy and affected family members confirmed the co-segregation of the variant with ARNSHL. Eventually, the variant's pathogenicity was confirmed by the in silico analysis and the ACMG/AMP guidelines. Conclusion The study suggests that the detected variant, c.499G>A, plays a crucial role in the development of ARNSHL, emphasizing the clinical significance of the ESRRB gene in ARNSHL patients. Additionally, it would be helpful for genetic counseling and clinical management of ARNSHL patients and providing preventive opportunities.